Differential diagnosis of Norrie disease and X-linked familial exudative vitreoretinopathy (XL-FEVR) based on clinical and molecular evaluation - Wawrocka, Anna; Niedziela, Zuzanna; Skorczyk-Werner, Anna; Krawczynski, Maciej R. (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Background : Molecular analysis of the NDP gene to confirm and precise the clinical diagnosis in two patients with X-linked familial exudative vitreoretinopathy (XL-FEVR). Material and methods : We report two patients from unrelated families with NDP gene mutations: a 14-month-old boy (p1) who was found to have severe exudative vitreoretinopathy and a 4-year-old boy with exudative vitreoretinopathy (p2). An extensive clinical examination of the probands, including slit-lamp examination, B-mode ultrasonography and magnetic resonance imaging was conducted, along with genetic analysis of NDP gene. Results : Clinical findings in patient 1 included no light perception, total retinal detachment and hyperplastic primary vitreous in both eyes. The genetic analysis of the NDP gene enabled to identify the novel frameshift mutation c.222_c223insCG in p1 leading to the premature stop codon and production of aberrant norrin protein. In P2, clinical presentation included high myopia with astigmatism, unilateral fibrous bands and retinal detachment. Genetic testing revealed known point mutation c.362G>A leading to amino-acid alteration and improper protein. Conclusions : Mutation screening of NDP gene identified two different mutations in this region, one of which has not been previously reported.